Narrative Literature Review: Konsep Pengembangan Sumber Daya Manusia di Era Digital - Umar Khasan; Teguh Soedarto (Eco-Entrepreneur, 2025)
The purpose of this research is to explain the concept of human resource management and how to develop human resources in the digital era. The research method in this study uses Narrative Literature Review. This research data was obtained through several journal articles with the keywords of human resource management concepts and human resource development in the digital era. Data analysis in this study used qualitative data analysis. The results show that the concept of human resource management is managing, developing, motivating, and evaluating the entire workforce needed by the company to achieve its goals. Then the development of human resources in the digital era that can be applied by organizations and companies includes digital training, the use of information systems (AI and IoT), flexibility in workforce management, innovation and company adaptation to new technologies.